Monetary theory and fiscal policy - Hansen, Alvin H. (New York : McGraw-Hill Book Co., 1949)
This book gives a comprehensive descriptive analysis of money and banking institutions but devote very limited attention to the theory of money and prices. It also considers the riches of classical economics as well as neo-classical and Keynesian economics in discussing fiscal policy and international economics.
Includes index
Bibliography: p. 227-230.
usc 08/10/18
Loans
Keywords: Money; Currency question; Fiscal policy; Prices